UPLB gold a new durian selection - Namuco, Leon O. (1999)
Durian 'UPLB Gold' was developed from a seedling tree of unknown parentage and it won a national award as Best Durian Selection in 1995. It is an early-season variety and a prolific bearer. During the past 6 years, the original tree yielded an average of 58 fruits (116 kg) per fruiting season. Its fruits are small and oblong. It has a thick peel. Its aril is bright yellow, very creamy, thick and very sweet with mild aroma. It has 7-8 well developed seeds. Edible portion is about 25%. The fruit is tolerant to wet core and uneven fruit ripening. It is easily propagated by cleft grafting.
Keywords: Durian (Fruit)